An Analysis of the Meaning of Slander from the Perspective of Tafsir al-Qurtubi - Roswati, Ai; Nidhom, Khoirun; Ghifari, Muhammad (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2025)
The word “fitnah” in the Qur'an has diverse and contextual meanings, so it requires in-depth exploration to understand its dimensions and implications. Through text analysis method and hermeneutic approach, this study explores Al-Qurtubi's interpretation of the verses containing the word “fitnah”. The word “fitnah” in the Qur'an has a broad and diverse meaning, depending on the context of the verse. According to Imam Al-Qurtubi in his tafsir book, “Al-Jami' li Ahkam Al-Qur'an”, the word “fitnah” and its derivatives are mentioned in various forms, including verbs (fi'il), nouns (isim), and adjectives. “fitnah” and its derivatives are mentioned around 60 times in the Qur'an. However, this number may vary depending on the way the word is counted and interpreted. The word fitnah in its base form (isim) is mentioned 34 times in the Quran and in its verb (fi'il) and adjective forms is mentioned 26 times in the Quran. The results showed that Al-Qurtubi interpreted fitnah in various contexts, such as tests, trials, chaos, misguidance, and torment. This study also reveals the importance of historical, linguistic, and social contexts in Al-Qurtubi's interpretation, as well as the relevance of the concept of fitnah in contemporary life. Kata "fitnah" dalam Al-Qur'an memiliki makna yang beragam dan kontekstual, sehingga membutuhkan eksplorasi mendalam untuk memahami dimensi dan implikasinya. Melalui metode analisis teks dan pendekatan hermeneutika, penelitian ini mengeksplorasi interpretasi Al-Qurtubi terhadap ayat-ayat yang mengandung kata "fitnah". Kata "fitnah" dalam Al-Qur'an memiliki arti yang luas dan beragam, tergantung pada konteks ayatnya. Menurut Imam Al-Qurtubi dalam buku tafsirnya, "Al-Jami' li Ahkam Al-Qur'an", kata "fitnah" dan turunannya disebutkan dalam berbagai bentuk, termasuk kata kerja (fi'il), kata benda (isim), dan kata sifat. "fitnah" dan turunannya disebutkan sekitar 60 kali dalam Al-Qur'an. Namun, angka ini dapat bervariasi tergantung pada cara kata tersebut dihitung dan ditafsirkan. Kata fitnah dalam bentuk dasarnya (isim) disebutkan 34 kali dalam Al-Qur'an dan dalam kata kerja (fi'il) dan bentuk kata sifatnya disebutkan 26 kali dalam Al-Qur'an. Hasil penelitian menunjukkan bahwa Al-Qurtubi menafsirkan fitnah dalam berbagai konteks, seperti ujian, cobaan, kekacauan, kesalahan, dan siksaan. Penelitian ini juga mengungkapkan pentingnya konteks sejarah, bahasa, dan sosial dalam interpretasi Al-Qurtubi, serta relevansi konsep fitnah dalam kehidupan kontemporer.